Clinical prognostic value of isocitrate dehydrogenase mutation, O-6-methylguanine-DNA methyltransferase promoter methylation, and 1p19q co-deletion in glioma patients - Chen, Xi (Ann Transl Med, 2019)
BACKGROUND: Gliomas are the most frequently occurring malignant brain cancers. Recently, isocitrate dehydrogenase (IDH) mutations, O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation, and 1p/19q co-deletion have been suggested to indicate a favorable prognosis in gliomas. However, the clinical prognostic value of these genetic tests in human gliomas is not fully understood. METHODS: We included glioma patients who accepted genetic testing including IDH, MGMT and 1p/19q at Xiangya Hospital, Central South University in China (Jan 2015 to Jun 2017) and further analyzed the effect of the above gene states in high-grade gliomas. RESULTS: In 103 high-grade glioma patients, IDH mutation, MGMT promoter methylation, and 1p/19q co-deletion had better progression-free survival (PFS) than IDH wild-type (P=0.005), MGMT unmethylated promoter (P=0.002), and without 1p19q co-deletion (P=0.008), respectively. Additionally, we classified the above gliomas into 5 molecular groups, triple-positive, IDH mutation and MGMT methylation, methylation in MGMT only, mutation in IDH only, and triple-negative, according to characteristics of recruited patients. We found that triple-positive gliomas had better PFS than triple-negative cases in high-grade patients (P=0.016). Moreover, the IDH mutation and MGMT methylation groups had prolonged PFS compared to triple-negative (P=0.029). CONCLUSIONS: Our study reinforced the clinical value of biomarkers, including 1p/19q co-deletion, IDH mutation, and the most prominent MGMT methylation, as previously described in glioma prognosis. Further, triple-negative patients have poorer PFS, indicating that the states of these genes can be divided into subgroups as a potential prognostic marker for clinical treatment, which requires a larger, multicenter study to testify.